Locally administered liposomal drug depot enhances rheumatoid arthritis treatment by inhibiting inflammation and promoting cartilage repair - Zongquan Zhang; Guan Wang; Zhuo Zhang; Xiaoya Liang; Guoshuang Wang; Maochang Xu; Xi Yang; Xiaolin Zhong; Chunhong Li; Meiling Zhou (Journal of Nanobiotechnology)
Abstract Rheumatoid arthritis (RA) is a chronic autoimmune condition characterized by synovial hyperplasia, where inflammatory macrophages within the joint synovium produce multiple inflammatory cytokines, leading to cartilage damage. The development of therapeutic strategies that combine anti-inflammatory effects and cartilage repair mechanisms holds great promise for effective RA treatment. To address the limitations associated with the off-target effects of intravenous administration and the risk of synovial cavity infection with repeated local injections, we have innovatively developed a liposomal drug depot through hyaluronic acid (HA)-modified liposomes encapsulating dexamethasone sodium phosphate (DSP)-loaded nanogels, termed HA-Lipo@G/D. The nanogels were prepared by ionic cross-linking of chondroitin sulfate and gelatin, both of which have notable cartilage repair properties. In vitro studies demonstrated that this formulation exhibited sustained drug release, enhanced uptake by inflammatory macrophages, reduced secretion of inflammatory factors (TNF-α, IL-1β), and significantly decreased chondrocyte apoptosis induced by inflammatory factors. Moreover, in vivo assessments in a rat model of collagen-induced arthritis revealed effective accumulation of the liposomal drug depot at the inflamed joint site, resulting in macrophage repolarization and cartilage tissue repair. Our findings provide a synergistic strategy for inhibiting inflammation and mitigating cartilage damage through local joint cavity injection, thereby enhancing the therapeutic efficacy of RA. Graphical Abstract